Fully-coupled modelling and experimental validation of quarter wavelength resonator with piezoelectric backplate in vibro-acoustic energy harvesting - Muhammad Hatifi, Mansor; Mohd Shahrir, Mohd Sani; Mohd Firdaus, Hassan; Tang, Lihua (Penerbit Universiti Malaysia Pahang, 2025)
Converting and harvesting the unwanted sounds produced by noise, especially in busy cities, can solve the issue of sound pollution and provide renewable power sources for low-power electronics. Although sound energy is freely available, it is hard to harvest due to its relatively low energy density compared to other sources. To enhance the efficiency of acoustic energy harvesting, particularly in the low-frequency range. The intgration of an optimised resonator is essential. This research study explores the performance of a vibroacoustic energy harvester incorporating a straight tube quarter-wavelength resonator coupled with a piezoelectric patch mounted on a flexible backplate. A fully coupled finite element model (FEM) was developed to capture the interaction between acoustic field, structural dynamic and piezoelectric transduction, and its predictions were validated against experimental results. The numerical model yielded a maximum output voltage of 1.41 V/Pa at 112 Hz, closely matching experiment findings of 1.44 V/Pa at 106 Hz under an incident sound pressure level of 90 dB. The proposed modelling framework demonstrates strong predictive capability and provides a robust basis for the design and optimisation of low-frequency acoustic energy harvester based on quarter-wavelength resonator configuration.